Angiogenin abolishes cell-free protein synthesis by specific ribonucleolytic inactivation of ribosomes. - St Clair, D K (1987)
Angiogenin is a potent inhibitor of cell-free protein synthesis. When incubated with rabbit reticulocyte lysate at a concentration of 40-60 nM, it completely abolishes the capacity of the lysate to support protein synthesis. The inhibition appears to be due to its ribonucleolytic activity since it (i) generates limited cleavage products from reticulocyte RNA and (ii) is prevented from both cleaving RNA and inhibiting protein synthesis by placental RNase inhibitor. The ribonucleolytic activity of angiogenin toward the reticulocyte RNA system is highly specific. Thus, under conditions where angiogenin totally abolishes protein synthesis, an equivalent concentration of pancreatic RNase A inhibits it only partially. In contrast, RNase A is a much more effective enzyme than angiogenin using isolated RNA as substrate. Angiogenin inhibits protein synthesis by cleaving rRNA, thereby inactivating the protein synthesis machinery. Addition of isolated reticulocyte ribosomes to an angiogenin-treated lysate restores the capacity for protein synthesis, whereas addition of tRNA or mRNA does not. This potent effect on protein synthesis suggests a possible physiological function of angiogenin whose overall relevance and implications should become evident as the mechanisms of neovascularization are deciphered. The use of angiogenin may also further elucidate ribosome structure and its role in protein synthesis.